SATAW: sistema de automatização de testes para aplicações web - Calisto Junior, Aramis (2012)
The search by tools that automate process is a mundial tendency also present in software industry. The SATAW is a tool developed based on a innovate idea for web application test tools. Providing reduction of costs and time of developed. The SATAW is based on automatic test generation into wanted web-site. Where to user can register your application and make some configurations. This system was been developed with focus into simplicity and automation.